2017
DOI: 10.15644/asc51/2/5
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status Related to Social Behaviors among 6 - 11 Year Old Schoolchildren in Kosovo

Abstract: AimThe aim of the present study was to evaluate the current oral health status among schoolchildren in Kosovo aged 6-11 years.Material and methodsA study included 5679 schoolchildren aged 6 -11 years, from different towns of Kosovo. Dental health status was evaluated using the World Health Organization (WHO) caries diagnostic criteria for decayed, missing and filled teeth (dmft/DMFT index), for deciduous and permanent dentition. The observed children have answered a number of questions about their oral hygiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies, low frequency of oral hygiene practices associated with poor oral hygiene and a high frequency of oral hygiene practices associated with less gingival bleeding [37, 38]. In addition a high frequency of intake of biscuits and carbonated soft drinks was associated with dental caries (DMFT> 0) and dental erosion, respectively [35, 39]. Not surprisingly, those who reported to clean their teeth less often, had poorer oral hygiene status and more gingival bleeding compared to those who cleaned more often [40].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies, low frequency of oral hygiene practices associated with poor oral hygiene and a high frequency of oral hygiene practices associated with less gingival bleeding [37, 38]. In addition a high frequency of intake of biscuits and carbonated soft drinks was associated with dental caries (DMFT> 0) and dental erosion, respectively [35, 39]. Not surprisingly, those who reported to clean their teeth less often, had poorer oral hygiene status and more gingival bleeding compared to those who cleaned more often [40].…”
Section: Discussionsupporting
confidence: 89%
“…The results from the present study show that oral health of children with type 1 diabetes in Kosovo is a serious health problem. Previous studies conducted in Kosovo regarding dental caries among children and healthy adults reported high scores of dental caries [ 21 24 ]. In our study, the prevalence of dental caries was significantly higher among diabetic patients than nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study sample cannot be regarded a representative of the entire population, due to the reasonably small sample size among healthy children. Though, since an earlier study, conducted in Kosovo, reported a DMFT score of 4.36 ± 3.76 among 6-11-years old [25]. The results from our study strongly recommend that there is an urgent need for community-based strategies for caries disease control in Kosovo.…”
Section: Discussionmentioning
confidence: 40%